Transport systems telematics 10th conference, TST 2010, Katowice - Ustroń, Poland, October 20-23, 2010. Selected Papers - International Conference "Transport Systems Telematics TST" Katowice and Ustroń, Poland) 2010; Mikulski, Jerzy; SpringerLink (Online service). (New York Springer, 2010)
This book constitutes the proceedings of the 10th Conference on Transport Systems Telematics, held in Katowice-Ustron, in October 2010.
Keywords: Telematics -- Congresses; Transportation -- Communication systems -- Congresses; Telecommunication -- Technological innovations -- Congresses; Electronic books